2018
DOI: 10.1155/2018/5840761
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Wind‐Induced Noise of High‐Rise Building Curtain Wall with Outside Shading Devices

Abstract: Perforation metal plates with dense holes are often used as external curtain walls of high-rise buildings. When air flow passes through these holes at a high speed, complex vortex is generated and causes a significant issue of wind-induced noise. In this study, both Reynolds-averaged Navier–Stokes (RANS) simulations and large-eddy simulations (LES) were conducted to study flow around high-rise buildings with an external sunshade curtain wall. First, wind speed distributions at the height of a typical level und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…fences, cables, towers, buildings, smoke stacks, etc. (Bolduc & Bell 2018;Xu & Xu 2018)). In the far field, regarding sound-wave patterns, previous studies (Gerrard 1955;Etkin, Korbacher & Keefe 1957) showed that the sound exhibits a dipole nature, which consists of a predominant fundamental frequency accompanied by several harmonics, and that the fundamental tone radiates most strongly in the direction perpendicular to the free stream direction, while the first harmonic radiates most strongly in the free stream direction.…”
Section: Introductionmentioning
confidence: 99%
“…fences, cables, towers, buildings, smoke stacks, etc. (Bolduc & Bell 2018;Xu & Xu 2018)). In the far field, regarding sound-wave patterns, previous studies (Gerrard 1955;Etkin, Korbacher & Keefe 1957) showed that the sound exhibits a dipole nature, which consists of a predominant fundamental frequency accompanied by several harmonics, and that the fundamental tone radiates most strongly in the direction perpendicular to the free stream direction, while the first harmonic radiates most strongly in the free stream direction.…”
Section: Introductionmentioning
confidence: 99%